A gestão de resíduos sólidos: utopia ou realidade no estado do Tocantins? - Santos, Robson Tiburcio dos (Universidade Federal do Tocantins, 2019)
The objective of this work is to address the standards for solid urban waste management in Brazil. For this purpose, the classification of the waste and its final disposition was adopted, emphasizing the performance of the Public Prosecutor's Office and the Court of Accounts of the State of Tocantins as State agents who have the institutional mission to comply with and enforce the commands of the National Policy of Solid Waste, Federal Law No. 12,305 / 2010. This legal framework, which, among other purposes, inaugurates the shared responsibility between public power and society in the solid waste theme, reinforcing the need to implement the culture ofselective collection and environmental education as guiding elements for reducing the volume of material released in the various landfill models. It was observed that actions developed in this follow-up count on financial resources made available by the Federal Government through the National Health Foundation, however, the concreteness of these actions in the municipalities depends on the engagement of the local managers to capture the values offered and the conviction of these local administrators who treat it with the public thing on solid waste also contributes to preservation of the environment ecologically balanced for the present and future generations as well as will maintain (political and patrimonial) rights ifthey comply with the National Policy of Solid Waste demarcated on August 02, 2010.